Molecular Method Optimization to Identify Plasmodium falciparum Multidrug Resistance 1 (pfmdr1) gene as a Predictor of Antimalarial Resistance - Erma Sulistyaningsih; Rosita Dewi; Sheilla Rachmania; Irawan Fajar Kusuma; Muhammad Rizqi Kholifaturrohmy; Yunita Armiyanti; Sakinatus Sariroh Kholifaturrohmah; Made Prasanti Andriani (Biology, Medicine, & Natural Product Chemistry, 2025)
Several approaches have been designed to control malaria, a disease with high morbidity and mortality, but they face some hurdles. Antimalarial resistance is one of the major challenges for malaria elimination, so the detection of antimalarial resistance is essential. Several molecular markers for antimalarial resistance have been identified, including Plasmodium falciparum multidrug resistance 1 (pfmdr1) gene. This study determined the optimization of molecular techniques to identify the pfmdr1 gene as an antimalarial resistance predictor in Indonesia. The study included patients diagnosed with uncomplicated or severe malaria originating from the health district of Kerom Regency, Papua Province, and Dr. Soebandi Hospital, Jember, East Java Province. Blood samples were collected in the Whatmann filer paper after informed consent. DNA was isolated from dried blood filter paper, and nested PCR was performed using a specific primer, the pfmdr1-A and pfmdr1-B genes. The PCR cycle was optimized based on previous studies. The pfmdr1-A has a similar setting to the earlier study, but the pfmdr1-B had a different optimum setting from the previous study with the annealing temperature of 57oC for nested-1 and 62oC for nested-2. This PCR setting could be used for further examination. The positive results of the amplification indicated the potential for antimalarial resistance in the parasite population. A study on the gene copy number and polymorphism is essential to determine the definitive conclusion on antimalarial resistance.